DIGITAL FORENSICS IN UNCOVERING FRAUD PRACTICES BASED ON MONEY LAUNDERING SCHEMES IN DIGITAL FINANCIAL TRANSACTIONS - Nurillah, Isma; Banjarani, Desia Rakhma; Siagian, Putri Rumondang; Ervita, Mona (TANJUNGPURA LAW JOURNAL, 2026)
Abstract The development of digital financial transactions has opened up new space for fraudulent practices that no longer stand as a single criminal act, but are often arranged through money laundering schemes to disguise the origin of funds from crimes. In this context, perpetrators use layered accounts, digital wallets, payment gateways, crypto assets, fake identities, and cross-platform fund transfers to break the connection between victims, perpetrators, and fund flows. This study aims to analyze the role of digital forensics in uncovering fraudulent practices based on money laundering schemes in digital financial transactions, especially in tracking digital evidence, reconstructing transaction patterns, and strengthening legal evidence. This research shows that digital forensics plays an important role in uncovering transaction trails, analyzing metadata, tracing inter-account relationships, mapping placement, layering, and integration patterns, and maintaining the integrity of evidence through accountable acquisition, preservation, analysis, and reporting procedures. Digital forensics also helps uncover the construction of fraud disguised through digital financial transactions, so that proof rests not only on the victim's losses, but also on the systematic relationship between fraud modes, fund flows, and attempts to disguise the proceeds of crime. The contribution of this research lies in the argument that digital forensics needs to be placed as a strategic instrument in criminal law enforcement that is integrated with money laundering schemes, as well as as a basis for strengthening regulations, investigative capacity, and the validity of digital evidence-based evidence. Abstrak Perkembangan transaksi keuangan digital telah membuka ruang baru bagi praktik penipuan yang tidak lagi berdiri sebagai tindak pidana tunggal, melainkan sering disusun melalui skema pencucian uang untuk menyamarkan asal-usul dana hasil kejahatan. Dalam konteks tersebut, pelaku memanfaatkan rekening berlapis, dompet digital, gateway pembayaran, aset kripto, identitas palsu, serta transfer dana lintas platform untuk memutus keterhubungan antara korban, pelaku, dan aliran dana. Penelitian ini bertujuan untuk menganalisis peran digital forensik dalam mengungkap praktik penipuan berbasis skema pencucian uang pada transaksi keuangan digital, khususnya dalam pelacakan bukti digital, rekonstruksi pola transaksi, dan penguatan pembuktian hukum. Penelitian ini menunjukkan bahwa digital forensik berperan penting dalam mengungkap jejak transaksi, menganalisis metadata, menelusuri hubungan antar-akun, memetakan pola penempatan , layering , dan integrasi , serta menjaga integritas bukti melalui prosedur akuisisi, preservasi, analisis, dan pelaporan yang dapat dipertanggungjawabkan. Digital forensik juga membantu mengungkap konstruksi penipuan yang disamarkan melalui transaksi keuangan digital, sehingga pembuktian tidak hanya bertumpu pada kerugian korban, tetapi juga pada hubungan sistematis antara modus penipuan, aliran dana, dan upaya penyamaran hasil kejahatan. Kontribusi penelitian ini terletak pada argumentasi bahwa Digital forensik perlu ditempatkan sebagai instrumen strategi dalam penegakan hukum tindak pidana kejahatan yang terintegrasi dengan skema pencucian uang , sekaligus sebagai dasar penguatan regulasi, kapasitas investigasi, dan validitas pembuktian berbasis bukti digital. Kata kunci: Digital forensik, Keuangan Digital, Pencucian Uang, Penipuan.